2015
DOI: 10.1007/s00247-015-3307-y
|View full text |Cite
|
Sign up to set email alerts
|

Data quality in diffusion tensor imaging studies of the preterm brain: a systematic review

Abstract: BackgroundTo study early neurodevelopment in preterm infants, evaluation of brain maturation and injury is increasingly performed using diffusion tensor imaging, for which the reliability of underlying data is paramount.ObjectiveTo review the literature to evaluate acquisition and processing methodology in diffusion tensor imaging studies of preterm infants.Materials and methodsWe searched the Embase, Medline, Web of Science and Cochrane databases for relevant papers published between 2003 and 2013. The follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 98 publications
(37 reference statements)
0
6
0
1
Order By: Relevance
“…The observation that DTI indices obtained at termequivalent age imply retarded WM maturation in preterm infants has been made in other studies. 9,10 Many have focused on selected WM regions, often the PLIC, CST, or CC (see Table 2). However, there have been limited efforts to combine T2, in particular, so the anisotropy of T2, with DTI, across an entire WM atlas, to build a high statistical power classifier for prematurity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that DTI indices obtained at termequivalent age imply retarded WM maturation in preterm infants has been made in other studies. 9,10 Many have focused on selected WM regions, often the PLIC, CST, or CC (see Table 2). However, there have been limited efforts to combine T2, in particular, so the anisotropy of T2, with DTI, across an entire WM atlas, to build a high statistical power classifier for prematurity.…”
Section: Discussionmentioning
confidence: 99%
“…8 Diffusion tensor imaging (DTI) has been applied in studies of the developing brain, with the consistent result that diffusivities reduce rapidly, and fractional anisotropy (FA) increases rapidly, with GA across WM, though the rate and marginal mean is regionally dependent. 9,10 Decreasing radial diffusivity (RD) and increasing FA are reflective of the tortuosity imposed on water motion by the myelin sheath. Axial diffusivity (AxD) generally remains higher, decreasing more slowly.…”
Section: Introductionmentioning
confidence: 99%
“…Computation of voxel-wise CN variations could disclose this, hence holding significant promise for improving the reliability and interpretation of DTI analyses. Insufficient means or mere absence of quality control to avoid artefactual data in DTI (Jones and Cercignani, 2010) has recently raised concerns among clinical research community (Heemskerk et al 2013;Pieterman et al, 2015;Roalf et al, 2016), and it is obvious that such procedures will need to become standard components of future guidelines of evidence based clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, these differences were caused by an update of the search strategies by the authors. For example, in the review by Pieterman et al, 17 references were not found in our EndNote library, as they were of a later publication date than the last search date in our system. When correcting the data in the ESM results for the references not retrieved via our database searches, the number of included references showed only minor changes and the difference was still statistically significant.…”
Section: Discussionmentioning
confidence: 99%